Harvest Index and its Relationship with Runner Yield in Swamp Taro (Colocasia esculenta (L.) Schott.) - Roy Chowdhury, S.; Brahmanand, P. S.; Kumar, Ashwani (JOURNAL OF ROOT CROPS, 2013)
Dry matter production and runner yield of five swamp taro cultivars, viz., BCST 23, BCST 21, BCST 2, BCST 4 and BCST 15 were studied by growing them in marshy water-logged conditions at Directorate of Water Management, Bhubaneswar, Odisha, India. The cultivar BCST 15 produced significantly highest total runner yield and runner dry matter production at 6 and 9 months after planting (MAP). The total runner yield was the lowest in BCST 2. In BCST 15 greater proportion of dry matter was diverted to the leaf and petiole at the grand growth period, i.e. 6 MAP. However, exponential increase in runner dry matter with increase in harvest index both at 6 and 9 MAP suggested that harvest index could be used as a reliable selection index in breeding rogramme for increasing runner dry matter and yield in swamp taro.